Assessing the Impact of Watershed Management Interventions on Livelihood of Small- Scale Farmers and Ecosystem Services in Choke Mountains, East Gojjam Zone of Amhara Region, Ethiopia (Global Journal of Science Frontier Research, 2020)
In Ethiopia, natural resources management interventions have been implemented since the 1980s to restore degraded landscapes. However, little efforts have been made to investigate the impacts of natural resources management interventions on ecosystem services and livelihood. This study was conducted in the Choke Mountain, Northern Ethiopia, to investigate the effects of community-based watershed management interventions on ecosystem services and livelihood of smallholder farmers. Both qualitative and quantitative methods were used to collect and analyze data. The results indicated that deforestation, population pressure, topography, overgrazing, and continued cultivation are major causes of land degradation. Consequences of land degradation include a reduction in farm size, a decrease in soil fertility and crop production, drought, food insecurity, and poverty. Also, the results demonstrated that a shortage of clean water and a decline in vegetation composition are among the impacts of land degradation on ecosystem services.
Keywords: benefit-sharing; land degradation; local communities; watershed management interventions; participation